Adopt E-Learning for High School or Vocational School Students by Using Extended Unified Theory of Acceptance and Use of Technology - Trian Wahyu Prasetyo; Edwin Pramana; Hartarto Junaedi (Teknika, 2025)
This study uses the fundamental Unified Technology Acceptance and Use of Technology (UTAUT) model, which is based on earlier research, to identify potential characteristics that influence high school or vocational school students' success in embracing e-learning. The theoretical model is predicated on earlier studies that integrate elements from the UTAUT acceptance model with elements deemed pertinent to e-learning (computer anxiety and perceived enjoyment). 593 people from the Indonesian city of Gresik made up the sample. Theoretical models are developed and analyzed using structural equation modeling. Based on the examination of the six hypotheses put out, six of them can be accepted. Behavioral intention is positively and significantly impacted by performance expectancy, effort expectancy, social influence, facilitating conditions, and perceived enjoyment, while behavioral intention is negatively and significantly impacted by computer anxiety. Although there are numerous research models on the uptake of e-learning, internet, and computer use are already widely prevalent in developing nations like Indonesia. However, e-learning's acceptability in many educational sectors is still in its infancy, particularly among students in high school or vocational schools. Thus, this study offers a thorough analysis of the variables influencing Indonesian high school or vocational school students' acceptance of e-learning